Central‐Core Engineering of Dopant‐Free Hole Transport Materials for Efficient n‐i‐p Structured Perovskite Solar Cells. Issue 5 (10th April 2021) - Chang, Zhitao; Guo, Jiahao; Fu, Qiang; Wang, Ting; Wang, Rui; Liu, Yongsheng
Abstract : Replacing the dominating and dopant‐needing 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenylamino)‐9, 9′‐spiro‐bifluorene (spiro‐OMeTAD) with dopant‐free organic hole transport materials (HTMs) in n‐i‐p structured perovskite solar cells (PSCs) is a big challenge. Herein, a class of conjugated organic semiconductor materials, namely, ZT‐H1 and ZT‐H2, with unfused and fused core units, respectively, are successfully designed and synthesized for dopant‐free HTMs. It is found that the HTM ZT‐H1 exhibits a hole mobility of 7.08 × 10 −5  cm 2  V −1  s −1, which is improved to 5.16 × 10 −4  cm 2  V −1  s −1 for HTM ZT‐H2 due to the enlarged molecular planarity of ZT‐H2, leading to efficient intermolecular π–π interaction. Further investigation indicates that ZT‐H2 is more fit to facilitating hole extraction, restraining charge recombination, and guaranteeing long‐term stability of the devices. Consequently, a planar n‐i‐p structured device using ZT‐H2 as HTM without any dopants exhibits a remarkable efficiency of 19.63%, which is much higher than that of ZT‐H1‐based devices (10.64%). Importantly, ZT‐H2‐based devices are much more stable than the control devices using ZT‐H1 or spiro‐OMeTAD as the HTM. The findings reveal that the fused central core unit with extended π‐conjugation is an efficient strategy for rationally designing dopant‐free HTMs toward stable and efficient PSCs. Abstract : The structure–properties relationships of hole transport materials (HTMs) with fused and unfused core units are investigated. The HTM with a fused core exhibits a high hole mobility and an efficient charge extraction capability, leading to a remarkable efficiency of 19.63% when it is used as an HTM without any dopant, much higher than unfused HTM‐based devices (10.03%).